THE IMPACT OF INNOVATIVE MECHANISMS IN ATTRACTING FOREIGN INVESTMENT - Shayakubov Shakhzod Shakabilovich (Journal Park Publishing, 2022)
This article presents the structure of innovative mechanisms for attracting investment to the country, provides feedback from local and foreign scholars in the field of investment, as well as analyzes data on the investment potential of the Republic of Uzbekistan. In turn, the article also contains the author’s own views and scientific opinions.
Keywords: investment mechanism; investment flow; recipient